Hydrogen generation and utilization in a two-phase flow membraneless microfluidic electrolyzer-fuel cell tandem operation for micropower application. (1st January 2022) - Samir De, Biswajit; Cunningham, Joshua; Khare, Neeraj; Luo, Jing-Li; Elias, Anastasia; Basu, Suddhasatwa
Highlights: Microfluidic electrolysis cell and fuel cell ( µ EC- µ FC) tandem operation. Optimized electrolyte flow rate 1.4 mL min −1 in µ EC- µ FC membrane-less operation. The energy conversion efficiency is 99.98% for the µ EC at 2.5 V. Fuel utilization efficiency of 50% achieved at 0.2 V for µ FC in tandem operation. The power density of 11.45–14.68 mW cm −2 obtained in the µ EC- µ FC. Abstract: Advances in device miniaturization, ranging from sensors to transmitters, are driving the need for micro-scaled personalized on-demand power sources. Herein, the tandem operation of a membraneless, two-phase flow microfluidic electrolysis cell and fuel cell ( µ EC- µ FC) is demonstrated, which is a step towards developing an independent micropower source. This device consists of a membraneless double Y-shaped microchannel that encompasses microelectrodes for the microfluidic electrolysis cell ( µ EC) and microfluidic fuel cell ( µ FC). A voltage applied to the µ EC induces two-phase flow in the µ EC- µ FC, resulting in the evolution of H2 and O2 gases that are transported to the µ FC by convection, and consumed to generate power. The catholyte-anolyte interface of the µ EC- µ FC behaves as a virtual membrane. The gas product mixing and crossover are averted by controlling the flow rate of electrolyte. Dimensionless numbers are used to characterize the flow in the microchannel. Tandem performance evaluation of µ EC- µ FC operation in acidic and alkaline electrolytes based on the flow rate (1.4 – 1.6 mL min −1 ) and µ EC operating voltages (2.3 – 2.5 V) is done by polarization and power density curves. The µ EC- µ FC exhibited 4 h of stable tandem operation. The µ EC exhibits 99.98% energy conversion efficiency, with the µ FC attaining up to 50% fuel utilization in tandem mode.